Misi Legio Maria Argo Karmel Di Tengah Dunia Urban Malang - Wekin, Oktavianus Klido (Perspektif, 2020)
The Legion of Mary has one mission, which is to proclaim Jesus Christ to the whole world through the Blessed Virgin Mary. A group of the Legion of Mary called ‘Legio Maria Argo Karmel’, headquartered in Malang, has been chosen as the place of this research. In its mission, the Legion has to cope with a lot of problems, particularly with the complex urban culture. The writer found out that the people in this urban area live in a complex world, such as plurality in ethnic backgrounds, cultures, races, as well as religions. It is a great challenge for members of the Argo Karmel Legion of Mary to carry out their mission. They are convinced, however, that they are called and sent to accomplish the mission entrusted to them by the Merciful God. To be more precise, it is their very missionto be witnesses of Christ in the midst of the complex urban city of Malang.